Profibrotic Inflammatory Cytokines and Growth Factors Are Predicted as the Key Targets of Uncaria gambir (Hunter) Roxb. in Keloids: An Epistatic and Molecular Simulation Approach - Sri Suciati Ningsih; Fadilah Fadilah; Sri Widia A. Jusman; Rahimi Syaidah; Takashi Yashiro (MDPI AG, 2024)
Keloid is characterized as the fibrotic tissue resulting from the increase of fibroblast activity. Uncaria gambir (Hunter) Roxb. possesses bioactive compounds that have potential as antifibrotic agents, while the mechanism of action in keloid has not yet been elucidated. The aim of this study was to investigate the interaction of gambir bioactive compounds with keloid target proteins using an epistatic and molecular simulation approach. The known bioactive compounds of gambir targets and keloid-related protein targets were screened using databases. The network was constructed and analyzed to obtain the core protein targets. The targets were enriched to describe the Gene Ontology (GO) and pathway related to the proteins. Eleven targets were defined as the main targets of gambir bioactive compounds related to keloid disease. Gambiriin C, Isogambirine, and Procyanidin B1 were identified as the most promising compounds with the highest binding energy to transforming growth factor beta 1 (TGFβ1), AKT serine/threonine kinase 1 (AKT1), and matrix metallopeptidase 1 (MMP1) as the target proteins. GO enrichment and pathway analysis found that gambir bioactive compounds may act on keloid-related target proteins to regulate cell proliferation, migration, transcription, and signal transduction activity via profibrotic cytokine and growth factor signaling pathways. This study provides a reference for potential targets, compounds, and pathways to explain the mechanism of gambir against keloid.